Morfem Bahasa Melayu Sub-Dilaek Desa Tanjung Hutan Kecamatan Buru Kabupaten Karimun - zakiah; Ahada Wahyusari; Dody Irawan (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research discusses the morpheme forms of Malay Sub-Dilaek, Tanjung Hutan Village, Buru District, Karimun Regency, based on morpheme forms that are often ignored by the local community and with the development of the times, technology has advanced rapidly, mixed with slang through social media. the only ones are TikTok, Instagram, and others. The aim of this research is to describe the forms of free and bound morphemes that exist in Tanjung Hutan Village, Buru District, Karimun Regency, Riau Islands. The method used in this research is descriptive qualitative. The data collection techniques used to obtain research data are tapping, listening and note-taking techniques. In analyzing the data, the technique used is translating the data obtained into Indonesian, systematically compiling the data obtained, classifying the free and bound morpheme data. After that, make a report from the results of data analysis and then draw conclusions from the data obtained. The results of this research reveal the process of free and bound morphemes from the Malay Sub-Dialect of Tanjung Hutan Village, Buru District, Karimun Regency, Riau Islands. The process of forming morphemes is broken down from 10 types of free morphemes, namely nouns, verbs, pronouns, adjectives, number words, adverbs, conjunctions, articles, interjections and prepositions, while there are 5 types of morphemes. bound. Free morphemes are nouns, verbs, pronouns, adjectives, number words, adverbs, conjunctions, articles, interjections and prepositions, while bound morphemes consist of prefixes (ber- and ter-) and infixes ( el-). Suffix (kan-) confix (senya) while simulfix (ng-, and ny-).